Minimum Competency Assessment Design to Improve Mathematical Literacy in Junior High Schools - ., Supandi; Ariyanto, Lilik; Kusumaningsih, Widya (KnE Social Sciences, 2022)
Mathematical literacy ability is important in the process of learning mathematics at schools. Efforts to improve mathematical literacy skills mostly involve providing materials and integrating learning with an ethnomathematical approach and higherorder thinking skills (HOTs) related to real life. The minimum competency assessment (AKM) is one of the ways to photograph students’ numeracy skills so that students can face and understand the flow of information. This study aims to design AKM tools for junior high school students in the city of Semarang, with a focus on mathematics. The study included the administrators of the association of mathematics teachers and all junior high school mathematics teachers in the city of Semarang. A large-scale focus-group discussion was created. The results show that the AKM design has a positive influence on teachers. Since teachers receive contextual information more quickly, the form of AKM questions becomes up to date. Students, on the other hand, are happy as the questions are presented in the form of stories. Thus, students’ mathematics learning ability increases, this is indicated by students being able to understand information from AKM questions. Keywords: mathematical literacy, minimum competency assessment, HOTs